2013
DOI: 10.1111/1471-0307.12024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ripening on proteolysis and lipolysis of Murcia al Vino cheese

Abstract: The aim of this study was to evaluate the influence of five different manufacturers and two ripening periods on the proteolysis and lipolysis patterns of Murcia al Vino goat cheese. The manufacturers significantly affected the water activity (aw), pH, dry matter and fat content, several nitrogen fractions: water soluble nitrogen (WSN), trichloroacetic acid (12% w/v) soluble nitrogen (TCASN) and phosphotungstic acid (5% w/v) soluble nitrogen (PTASN); also the free amino acid (FAA) and free fatty acid (FFA) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…; Boutoial et al . ). In relation to the latter factor, the acidification rate and the final pH may have affected the metabolism of the lactic acid bacteria, particularly the lactococcal strains present in the DL‐starters.…”
Section: Resultsmentioning
confidence: 97%
“…; Boutoial et al . ). In relation to the latter factor, the acidification rate and the final pH may have affected the metabolism of the lactic acid bacteria, particularly the lactococcal strains present in the DL‐starters.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the detected amount of this fatty acid in this study was higher than that reported by Katsiari, Voutsinas, Alichanidis, and Roussis () (0.85mg/100 g). According to Georgala et al (), high levels of C4:0 fatty acid in cheese point out the selective lipolytic activity, which plays a major role in the organoleptic characteristics of cheese and improves the flavor of the cheese (Boutoial et al, ). The highest and lowest amounts of C4:0 fatty acid, on day 90 of ripening, were detected in the control and TG2 samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Every type of cheese has a specific FAA composition, the concentration of which depends on production technology used, the extent and type of proteolysis, and the time and ripening conditions of each manufacturer (25). The total FAA content increased to 384.33 g kg −1 at the end of ripening.…”
Section: Resultsmentioning
confidence: 99%